The Rhetoric of the Polish Constitution of 1791: "The King with the Nation, the Nation with the King" - Kieran Stenson (The Owl)
On 3 May, 1788, three years before the promulgation of the Constitution of 3 May 1791, King Stanisław II August of Poland, Grand Duke of Lithuania, and possessor of a host of other titles, described a “fermentacya” among the youth of the Polish-Lithuanian Commonwealth, as the elected envoys of the Four-Years Sejm began their march into the political unknown.1 The Sejm was the parliamentary body of the Commonwealth, a complex, decentralized state which controlled vast swathes of Central and Eastern Europe roughly from 1569 to 1795. From 1788 to 1792 this legislative body became a political movement which attempted to reform the country. Emboldened by a temporarily favorable international situation, with Russia distracted by war with the Ottoman Empire, the new Sejm (Polish Parliament) launched an unprecedented movement of reform that eventually culminated in the Constitution of 3 May 1791. This was a revolutionary document, studied by generations of Polish and foreign historians. However, its creation was also the result of significant compromise, particularly between ‘enlightened republicans’ and the King. The Constitution’s articles and language reveal much about the political beliefs and ideology of this transformative period in Polish and Eastern European history.